The potential of triterpenoids as chemotaxonomic tools to identify and differentiate genuine, adulterated and archaeological balsams - Courel, Blandine; Adam, Pierre; Schaeffer, Philippe (Microchemical journal, 2019)
Plant exudates have been extensively used in the past for different applications related to their olfactory, physical or medical properties. Their identification in archaeological samples relies, notably, on the characterisation of chemotaxonomic molecular markers but is often hampered by the severe alteration of their typical genuine molecular signature due to ageing. Among these exudates, those recovered from Styrax, Liquidambar and Myroxylon tree species – defined as balsams – have been exploited in the past for their pleasant scent and medical properties. They are characterised by a large variety of aromatic compounds, especially of the cinnamate and benzoate series, which can be used to assess their botanical source. These compound series may, however, be subject to alteration over time during exposure to environmental conditions in the case of archaeological material. As a result, their reliability as chemotaxonomic markers to characterise and discriminate archaeological balsams is problematic and questionable. We have, therefore, carried out a comparative analysis of various extant balsams (Styrax officinalis, S. paralleloneurum, S. tonkinensis, Liquidambar styraciflua, L. orientalis and Myroxylon balsamum var. pereirae) using gas chromatography–mass spectrometry to search for more solid lipid markers. The results revealed that a distinction between styrax, liquidambars, Peru and Tolu balsams is possible based on the distribution of pentacyclic triterpenes. The predominance of uncommon 6‑oxygenated derivatives of oleanolic acid among triterpenoids could be specifically related to styrax resins. Liquidambar gums were characterised by the predominance of oleanonic acid together with uncommon 3-epi oleanolic and ursolic acids, whereas Peru balsam was rich in cinnamic and benzoic acids, but devoid of triterpenoids. Thanks to the high specificity of some of these triterpenes, already known for their low volatility and robustness towards alteration processes, they should be considered as reliable molecular tools for the unambiguous identification of archaeological balsams. In addition to archaeological applications, these triterpenic markers might also find an application for the detection of counterfeit balsams. •The distribution of phenylpropanoids can be used to differentiate fresh balsams (styrax, liquidambars and Peru balsam).•Triterpenoids are solid taxonomic tools to characterise archaeological and adulterated balsams.•Sumaresinolic acid and its derivatives, together with cinnamic and benzoic acid derivatives, are specific to Styrax species.•Oleanonic acid along with 3-epi oleanolic and 3-epi ursolic acids define Liquidambar gums.•No triterpenes were found in Peru balsam.